2007
DOI: 10.1039/b617427b
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin architecture dependence on the capture efficiency of antibody-modified microbeads by magnetic nanoparticles

Abstract: We show that the ability to control the architecture/orientation of vancomycin on the surface of magnetic nanoparticles has a drastic effect on the ability of the nanoparticles to magnetically confine vancomycin-antibody modified polystyrene microbeads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
(19 reference statements)
1
25
0
Order By: Relevance
“…With our covalent approach, 6 all carbohydrates are uniformly oriented on the NP surface, which is crucial for high performances in cell-capturing studies. 7 All MGNPs were characterized by X-ray diffraction, transmission electron microscopy (TEM), thermogravimetric analyses, and IR spectroscopy ( Figures S1-4).…”
mentioning
confidence: 99%
“…With our covalent approach, 6 all carbohydrates are uniformly oriented on the NP surface, which is crucial for high performances in cell-capturing studies. 7 All MGNPs were characterized by X-ray diffraction, transmission electron microscopy (TEM), thermogravimetric analyses, and IR spectroscopy ( Figures S1-4).…”
mentioning
confidence: 99%
“…A final 1% solution of succinic anhydride was used. 17 This solution was allowed to react overnight and was rinsed twice in THF the next day to remove any unreacted succinic anhydride. These carboxylate coated SPION ( Figure 1C) were stored under refrigeration in a THF solution where no observable oxidation was seen in a period of less than a month.…”
Section: Carboxylate Functionalized Spionmentioning
confidence: 99%
“…Recently, many studies have also demonstrated the use of magnetic particles coated with antibiotics as an alternative method for drug delivery, albeit such approaches still rely on the use of antibiotics for which bacteria are increasingly developing resistance towards. 12,17 In this study, superparamagnetic iron oxide nanoparticles (SPION) were functionalized with amine, carboxylic acid, or isocyanate groups and, for the first time, were tested for their ability to penetrate S. aureus biofilms to explore a novel non-antibiotic strategy to decrease bacteria growth after a biofilm is formed on a medical device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature has reported the use of vancomycin-functionalized magnetic nanoparticles as a noncovalent probe for capturing gram-positive bacteria. 29 Vancomycin is a pentapeptide glycoprotein antibiotic natural product that targets the D-alanine-D-alanine motif in gram-positive PG.…”
mentioning
confidence: 99%